Pelembagaan Mediasi Desa dan Sinergi Membangun Sistem Peradilan - Wawan Kokotiasa (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Institutionalization of village mediation is a strategic and synergistic endeavor with efforts to build a justice system in Indonesia. Especially in the perspective of access to justice for people in rural areas who experience disputes. Based on Law Number 6 of 2014, there are regulations that provide space and creativity for villages to institutionalize village mediation as "informal justice" to resolve disputes that arise in village communities. Besides, there are legal opportunities for village heads to take a strategic role in disputes that occur in village communities. Thus access to justice is closer to the villagers. Such a situation clearly synergizes with efforts to build a justice system that is accessible to all levels of society, is effective, efficient and is able to encourage the creation of an atmosphere of harmony in society.